Female Voices in Creatalks Entertainment Youtube Channel - I Putu Nanda Sheila Yudha; Stephen albert Waworuntu; Muizzu Nurhadi; Llilyanti Ina Bora; Steven Erduadus (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines how such voices are produced, circulated, regulated, represented, and given collective identity on the Creatalks Entertainment YouTube channel, using Stuart Hall's Circuit of Culture as its analytical framework. The Circuit of Culture conceives meaning-making as a continuous cycle linking five interdependent moments: production, consumption, regulation, representation, and identity. This study uses a qualitative case-study approach based on textual and thematic analysis of selected Creatalks episodes and their surrounding platform activity, this research finds that the channel's female narratives are shaped by a produsage-based production model, algorithm-sensitive platform governance, cultural and religious norms specific to the Indonesian context, dramatized modes of representation that reframe stigmatized experiences as public discourse, and a distinct audience identity built around empathy and communal acceptance. These five dimensions do not operate in isolation: production strategies invite audience participation, consumption practices generate diverse and at times conflicting interpretations, regulatory pressures negotiate between platform rules and local socio-religious values, representational choices reshape the visibility of taboo subjects, and identity formation consolidates a supportive audience community around the channel. The findings suggest that Creatalks functions less as a passive broadcaster of women's stories and more as an active cultural site where female voice, agency, and marginality are continuously negotiated among producers, platforms, and audiences. This study contributes to a broader understanding of how digital platforms in non-Western contexts mediate gender, stigma, and empowerment, and offers a basis for future research on audience reception and the ethics of presenting sensitive personal content online.